Appropriate nitrogen application under ridge-furrow plastic film mulching planting optimizes spring maize growth characteristics by improving soil quality in the Loess Plateau of China - Fan Zhang; Mengru Chen; Yingying Xing; Xiukang Wang (Agricultural Water Management)
Appropriate nitrogen application under ridge-furrow plastic film mulching planting (RF) is essential for improving crop growth characteristics and soil quality. Nevertheless, research on the effects of nitrogen application under RF on these factors, along with the underlying mechanisms, remains limited. A three-year spring maize field experiment was conducted using two planting methods (flat planting (FP) and RF) and four nitrogen application levels (0 (N0), 135 (N1), 180 (N2), and 225 (N3) kg ha−1) to investigate the effects on crop growth, yield, yield components, evapotranspiration (ET), water productivity (WP), nitrogen partial fertilizer productivity (NPFP), economic benefits, soil NO3-N residue at harvest, soil properties, and soil quality index (SQI). The results revealed that planting method and nitrogen application significantly affected crop growth, yield, yield components, ET, WP, NPFP, economic benefits, urease activity (SUA), phosphatase activity (SPA), catalase activity (SCA), sucrase activity (SSA), NO3-N residue, and SQI. Compared with FP, RF significantly improved crop growth, yield, economic benefits, ET, WP, NPFP, available potassium (AK), SUA, SPA, SCA, SSA, and SQI, and significantly reduced soil NO3-N residue and loss at maturity. The optimal crop growth, yield, hundred-grain weight, ET, WP, economic benefits, available phosphorus (AP), AK, organic matter (SOM), SUA, SPA, SCA, and SSA were observed at the N2 level. Treatment RFN2 exhibited superior improvements in crop growth, yield, economic benefits, resource use efficiency, soil properties, and SQI, regardless of annual precipitation levels. Soil properties exhibited highly correlated with crop growth characteristics, among which AP, SPA, SCA, and SUA were identified as critical soil factors for monitoring crop growth, yield, and WP. Notably, alkali-hydrolyzable nitrogen (SAHC), ammonium nitrogen (SANC), SUA, and nitrate nitrogen (SNNC) were key soil factors for monitoring NPFP. Our study revealed the mechanism by which nitrogen application under RF could improve yield and efficiency by regulating SQI. Given the factors of crop growth, yield, yield compositions, resource utilization efficiency, economic benefits, and SQI, the application of 180 kg ha−1 nitrogen under RF was recommended as a viable strategy for achieving high yield, high efficiency, and sustainable development of spring maize in the region. This research serves as a reference for the rational application of RF technology to improve farmland productivity and soil quality, thereby facilitating the sustainable development of the spring maize industry in China's Loess Plateau.